2014
DOI: 10.1016/j.ultsonch.2014.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Sonocatalytic and sonophotocatalytic degradation of rhodamine 6G containing wastewaters

Abstract: The present work deals with degradation of aqueous solution of Rhodamine 6G (Rh 6G) using sonocatalytic and sonophotocatalytic treatment schemes based on the use of cupric oxide (CuO) and titanium dioxide (TiO2) as the solid catalysts. Experiments have been carried out at the operating capacity of 2 L and constant initial pH of 12.5. The effect of catalyst loading on the sonochemical degradation has been investigated by varying the loading over the range of 1.5-4.5 g/L. It has been observed that the maximum de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(37 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…The results are consistent with the reported findings. The study of US-UV degradation of rhodamine 6G indicated that degradation increases with the addition of copper oxide; the maximum degradation of 52.6% was observed for (1.5 g/L loading of copper oxide) US-UV treatment and 26.4% for UV treatment at 12.5 pH of the solution (Bokhale et al 2014). Similar results reported for US-UV degradation of dye C.I.…”
Section: Effect Of Copper Oxidesupporting
confidence: 76%
See 2 more Smart Citations
“…The results are consistent with the reported findings. The study of US-UV degradation of rhodamine 6G indicated that degradation increases with the addition of copper oxide; the maximum degradation of 52.6% was observed for (1.5 g/L loading of copper oxide) US-UV treatment and 26.4% for UV treatment at 12.5 pH of the solution (Bokhale et al 2014). Similar results reported for US-UV degradation of dye C.I.…”
Section: Effect Of Copper Oxidesupporting
confidence: 76%
“…During photolysis, photon released from the UV source is absorbed by the water molecule and breaks the bond between the H Á and Á OH ions. Production of hydroxyl radicals during sonolysis depends on the liquid physiochemical properties of an aqueous medium, such as vapor pressure and surface tension (Bokhale et al 2014). Decolorization of BG enhanced on the multifold basis for the synergic combination of US-UV.…”
Section: Effect Of Us Uv and Us-uvmentioning
confidence: 99%
See 1 more Smart Citation
“…Although individual AOPs seem useful to treat textile wastewater, however they are also demonstrates substantially lower efficiency of degradation and complete mineralization especially for the complex effluent streams. The operation cost for this technique is also higher [6].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum degradation of 93% and 94% were achieved for photocatalysis, while 99.9% and 100% were obtained for sonocatalysis. These results suggested that the better efficiency of the combination processes of both irradiations compared to separately irradiation is not due to synergistic effects [14]. It is believed that sonolysis can increase the photocatalytic activity by: (i) increasing the catalytic activity of catalyst through the size reduction [15]; (ii) accelerating the mass transfer between the solution phase and catalyst surface [15].…”
Section: Resultsmentioning
confidence: 95%